Experimental investigation on instability characteristics of loss of heat sink accident in a natural circulation system. (1st June 2021) - Lin, Yuqi; Gao, Puzhen; Chen, Xianbing; Bello, Solomon; Tian, Chunping; Zhao, Chuncheng
Abstract: Loss of heat sink (LOHS) accident in a natural circulation system has a complex event sequence scenario. Flow instability phenomena in LOHS accident involves multiple flow patterns and variety instability mechanisms. Through experimental investigation, a methodology analyzing instability under LOHS is established. It is concluded while slug flow occurring in heating channel, the system falls into geyser instability region which is proven as pressure drop oscillations (PDO) accompanied by wave mode changing. While annular flow occurs, natural circulation system forms stable two-phase flow transitorily and losses stability again. The post-annular-flow instability cannot form a regular vibration wave mode, and annular flow absorbs flowrate oscillation instead of pressurizer. Finally, average flowrate approaches to 0 and critical heat flux (CHF) happens.